«The Great Patrician of the Speaking Art»: Cicero, from the Republic of Letters to the English Republic - Clare, Janet (Ciceroniana On Line, 2020)
This article explores the reception of Cicero in early modern England, specifically his centrality to the humanist education programme and as an exponent of civilizing rhetoric. It is contended that throughout the sixteenth century humanists were highly selective in their appreciation of Cicero to the extent that the political contexts and arguments of his oratory were largely ignored. The Cicero celebrated for De officiis (one of the most popular texts in England) was rarely joined to the Cicero of the Philippics, countenancing tyrannicide, even though these texts were composed within months of each other. The surge of interest in classical republicanism in the period of civil wars and the establishment of the English Republic in 1649 marked a decisive change in the representation of Cicero. The transition is exemplified in the play The Tragedy of that Famous Roman Orator Marcus Tullius Cicero (1651). Here, as a supporter of regicide and exponent of the freedom from a tyrannical state, Cicero’s political voice powerfully resonates across time and place.